Analysis of Students' Mathematical Concept Understanding Ability on Circle Material Based on Learning Style - Ilya Mahmudah; Sugiyanti Sugiyanti; Heni Purwati; Nika Dewi Indriati (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2024)
This research aims to analyze students' mathematical concept understanding ability in solving circle material problems by considering learning styles. The method used in this research is qualitative method with descriptive approach. This research was conducted on students of class XI Culinary 1 at SMKN 6 Semarang which amounted to 36 students. Data were collected through mathematical concept understanding test and student learning style questionnaire. The subjects in this study were three students who represented each student's learning style. The techniques used to collect data were observation, mathematical concept understanding ability test, interview and documentation. The results showed variations in learning styles and variations in students' mathematical concept understanding abilities in solving circle material problems. Learners with visual and auditory learning styles tend to have better understanding abilities in solving the problem, while learners with kinesthetic styles show different patterns. So it can be concluded that the learning style of learners can affect students' mathematical understanding ability in solving circle material problems, therefore the importance of recognizing the learning style of students in the mathematics learning process. Each learner with a different learning style has a different mathematical concept understanding ability, so an approach that is in accordance with the characteristics of learners is needed to improve students' mathematical concept understanding ability.